0437 Psychometric Evaluation of the Insomnia Severity Index in Nurses. (25th May 2022) - Emert, Sarah; Nagy, Samantha; Dietch, Jessica; Taylor, Daniel
Abstract: Introduction: This secondary analysis was conducted to examine the psychometric properties of the Insomnia Severity Index (ISI) in a sample of non-shift working nurses. Insomnia is a common sleep disorder and has been linked to poor physical, psychological, and cognitive outcomes and increased accidents. Unique features of this sample (e.g., long shifts, patient care, quick emergency response) create a need for population-specific validation of the commonly used ISI. Study I assessed convergent and discriminant validity between the ISI, sleep diary, and other sleep and psychosocial measures. Study II assessed the test-retest validity of the ISI. Methods: Participants (N = 289) were nurses from two regional hospitals in north Texas recruited for a parent study (268 females, M age = 40.67 years; SD = 11.03; 79.9% White) who completed daily sleep diaries and sleep and mental health screeners at four timepoints. Shift workers and participants who did not complete the ISI at baseline were excluded from the analysis. Results: The ISI had medium to large correlations with measures intended to establish convergent validity including sleep onset latency (r = .41), wake time after sleep onset (r = .40), sleep efficiency (r = -.45), sleep quality (r = .66), and sleep related impairment (r = .67). Examination of ISI items and analogous sleep diary parameters showed small to large correlations (rs = .13-.53). The ISI had small to large correlations with measures intended to establish discriminant validity including nightmares (r = .25), circadian preference (r = -.26), shiftwork-related disorders (r = .09) and PTSD (r = .36), depression (r = .69), anxiety (r = .51), and perceived stress (r = .43). The ISI demonstrated good test-retest reliability from baseline to 1-month (ICC = .88), 6-month (ICC = .77), and 11-month follow up (ICC = .74). Conclusion: The ISI demonstrated good psychometric properties and is a psychometrically strong measure for the assessment of insomnia severity in nurses. Overlap with psychological symptoms suggests caution while interpreting these constructs. Support (If Any): This study was supported by a grant from the National Institute of Allergy and Infectious Diseases, Grant/Award Number: R01AI128359‐01.